Papillary Renal Cell Carcinoma With Osteosarcomatous Heterologous Differentiation: A Case Report With Molecular Genetic Analysis and Review of the Literature. (December 2017) - Aird, John James; Nic an Riogh, Aisling U.; Fleming, Stewart; Hislop, R. Gordon; Sweeney, Paul; Mayer, Nick
Sarcomatoid differentiation can occur in all subtypes of renal cell carcinoma (RCC). In rare cases, heterologous differentiation has been described. We present a case of heterologous osteosarcomatous differentiation in association with sarcomatoid papillary RCC including an analysis of chromosomal copy number alteration. This is the first case to identify heterologous differentiation in association with papillary RCC. The patient was a 70-year-old man who had a mass in the right kidney. Speckled calcification was seen on computed tomography scan. Histological assessment demonstrated papillary RCC merging with areas of sarcomatoid change and malignant bone formation simulating osteosarcoma. Cytogenetic evaluation demonstrated additional copies of chromosome 7 in both epithelial and osteosarcomatous components. A literature review identified 33 previous cases of heterologous differentiation in association with RCC. Of the 14 cases that reported an epithelial subtype, 13 cases were reported to be chromophobe RCC and 1 case was reported to be clear cell RCC.